What and the how: content and communication of the one message, a consideration of the basis of faith, as formulated by the WCC - Hollenweger, Walter J. (The Expository Times, 1975)
The "What" and the "How" of a theological statement are related. If the "How" is the conceptual framework of the Western literary world, then the "What" is not expressed in universal terms. The ecumenical problem of the future is not the relationship between Catholic and Protestant theology, but the relationship between conceptual and narrative, between literary and oral theology. This ecumenical problem is exemplified in the history of the basis formula of the World Council of Churches, in its function (or non-function) during the German church struggle and in its relation to the first application by an African Independent church (the Kimbanguist church) for membership of the Council. The question of alternative, narrative and parabolic confessions is raised.
Keywords: Communication (Theology); Creeds; Developing countries – Religion; Kimbanguism; Peer reviewed; Witnessing; World Council of Churches